Dam break modeling and downstream flood inundation mapping on Darbandikhan Dam, Iraq - Khudhur, Isam Dhahir; Hamdan, Ahmed N. A. (Edelweiss Applied Science and Technology, 2024)
It is important to consider the catastrophic effects of dam collapses to make emergency and evacuation plans. This study simulates the hypothetical collapse of the Darbandikhan Dam in northeastern Iraq. Then, it routes the resulting flood from this collapse to the downstream region with an approximate length of 325 km. The flood impact was analyzed using the 2D HEC-RAS model with the help of ArcGIS software. The outflow peak discharge of the breach at the dam site reached approximately 381.1x103 m3/s. Inundation maps were created using RAS-Mapper, which contains the flood wave’s depth, velocity, and arrival time distribution through the study area. The maximum values of depth and velocity were (17.5-58) m and (2-22) m/s, respectively, in Sirwan district near the dam, with an arrival time (0.13-0.6) hr. The minimum values of depth and velocity were in the Al-Aziziyah district, which is located at the farthest point from the dam in the study area, which were (0-0.6) m and (0-0.3) m/s, respectively, with an arrival time of (169-186) hr. It is hoped that this research will contribute through its results to providing valuable data to enhance emergency preparedness and effective evacuation planning in the event of a dam failure.